Implementasi Metode Weighted Product Dalam Membantu Pengambilan Keputusan Penerima Beasiswa Pada SMK Amanah Uwung Tangerang - Rian Anggara; Nurul Adha Oktarini Saputri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The use of the Weighted Product Method in data processing that aims to assist decision making. Where the system can be utilized because it is adaptive, flexible, and interactive which is created and developed in order to assist in making decisions about an existing problem. The system used is expected to be useful in solving problems that exist in Amanah Uwung SMK Tangerang. In this system, criteria are needed in determining who will receive the scholarship. In this research process, the researcher uses the Weighted Product method. The reason for the researcher in choosing the Weighted Product method is that there is a process of determining the weight value for each criterion, and there is a ranking that will simultaneously select the alternatives that have been entered.